A torpedo is hoisted aboard the aircraft-carrier Furious after being launched in a mimic battle near the Canary Islands. Text on the back
A torpedo is hoisted aboard the aircraft-carrier Furious after being launched in a mimic battle near the Canary Islands. Text on the back.